Perilaku Komunikasi Siswa di Sekolah Homogen - Evelyn Faustina (Universitas Multimedia Nusantara, 2016)
Human communicate to fulfill their basic needs as social being. This communication ethnography research aims to see communication behavior between female students in Santa Ursula, a homogenous high school in Jakarta. The study also seeks to find the values and norms which can be seen through the students interaction. The data is analyzed using S-P-E-A-K-I-N-G model of Dell Hymes, an anthropologist who introduced the method of communication ethnography. The research shows that students in homogenous school create a social group with their own distinctive communication behavior and speech codes which were developed through frequent interactions between students. It can be concluded that the communication behavior of students in homogenous school is formed based on the characteristic of students who are accustomed to similar gender treatment and are tied by common norms. This communal group communicates any time, even outside formal or informal events. Keywords: communication behavior, homogenous school, communication ethnography